Graphene oxide microcapsules (GOMs) with linseed oil core via Pickering emulsion method effect of disperse speed - Sahir, Nurul Nadiah; Hassan, Noor Azlina; Hassan, Norita; Johari, Norhasnidawani (IIUM Press, International Islamic University Malaysia, 2021)
Graphene oxide microcapsules (GOMs) have been prepared through Pickering emulsion method by varying the disperse speed to study its effect on the GOM’s size. The GOMs were characterized through phase separation observation, polarized optical microscope (POM), and particle size analyser (PSA). Phase separation observation showed more viscous and cloudy emulsion was produced when the disperse speed was increased. After 24 hours, only 800 rpm emulsion did not show any phase separation. POM characterization depicted that increasing the emulsification energy led to the finer emulsion with the 1200 rpm sample showing the smallest microcapsule size of around 8 μm. However, PSA analysis suggested that although the disperse speed controls the GOMs size, the amount of GO in the emulsion plays an important role for the microcapsule to maintain its stability. Emulsion produced at 800 rpm possesses satisfactory stability with GOMs diameter of 11.15 μm. The result also suggested that graphene oxide encapsulated linseed oil may act as a promising candidate for healing microcapsules in a self-healing coating system. ******************************************************************************** Mikrokapsul graphene oksida (GOMs) telah dihasilkan melalui kaedah emulsifikasi Pickering dengan memvariasikan tenaga pengemulsi untuk mengkaji kesannya terhadap saiz GOMs. GOMs dicirikan melalui pemerhatian pemisahan fasa, mikroskop optik polarisasi (POM) dan penganalisis saiz zarah (PSA). Pemerhatian pemisahan fasa menunjukkan emulsi yang lebih likat dan keruh dihasilkan apabila kelajuan pengemulsi meningkat. Selepas 24 jam, hanya emulsi 800 rpm tidak menunjukkan pemisahan fasa. Pencirian POM meunjukkan bahawa peningkatan tenaga pengemulsi menghasilkan emulsi yang lebih halus dengan sampel 1200 rpm menunjukkan saiz mikrokapsul terkecil, sekitar 8 μm. Walau bagaimanapun, analisis PSA mencadangkan bahawa walaupun kelajuan pengemulsi mengawal saiz GOMs, jumlah GO dalam emulsi memainkan peranan penting untuk mengekalkan kestabilan mikrokapsul. Emulsi yang dihasilkan pada 800 rpm mempunyai kestabilan yang memuaskan dengan purata saiz GOMs sekitar 11.15 μm. Berdasarkan dapatan kajian, graphene oksida yang terkandung minyak biji rami boleh menjadi salah satu mikrokapsul penyembuh dalam sistem cat auto-sembuh.